Improving pediatric trauma care at a level 1 pediatric trauma center through the multi-year implementation of a Pediatric Trauma Boot Camp curriculum - Elizabeth M. Brigham; Erica I. Hodgman; Nicole A. Shilkofski; Justin M. Jeffers; Daniel An; Sean Tackett; Isam W. Nasr; Amanda B. Levin (Advances in Simulation)
Abstract Background Traumatic injuries are a significant contributor to pediatric morbidity and mortality, and trauma care necessitates that providers from different specialties and backgrounds be prepared to work together in high acuity settings to provide optimal care. Simulation-based trauma education consistently demonstrates improved knowledge, skill acquisition, teamwork, and task performance among providers, but relatively few studies assess provider performance during real resuscitations. The objective of this study is to develop an interdisciplinary pediatric trauma curriculum to improve trauma bay teamwork and adherence to ATLS ideals in the clinical environment. Methods We developed a simulation-based pediatric trauma curriculum (Pediatric Trauma Boot Camp) incorporating learners from multiple departments and divisions all of whom care for pediatric trauma patients at our institution. To determine the impact of the curriculum on trauma team clinical performance, videos of trauma activations throughout the multi-year implementation period were reviewed and data abstracted. Teamwork was assessed using the Trauma NOTECHS scale and ATLS compliance by the presence or omission of eight items of the primary and secondary survey. Eighty-six total trainees participated during 2 years of curriculum implementation with faculty from General Pediatric Surgery, Pediatric Emergency Medicine, and Pediatric Critical Care serving as facilitators. Results Out of a maximum of 25, the mean total Trauma NOTECHS score for the pre-pilot videos (n = 29) was 14.0. Post-pilot (n = 26), the mean total score improved to 16.8 (p = 0.001). Mean secondary survey completion improved from 4.1/8 pre-pilot to 5.4/8 post-pilot (p = 0.039). No significant difference was observed in primary survey completion between the first two cohorts. Following the second year of curriculum implementation, primary survey completion improved to 6.1/8 in the third cohort (n = 27) from 5.5/8 (p = 0.079). Continued improvement in total Trauma NOTECHS scores was observed (mean = 17.7), and improvements demonstrated in secondary survey completion were preserved. Conclusion An interdisciplinary simulation-based pediatric trauma curriculum incorporating learners across specialties has the ability to positively impact provider behavior and direct patient care at a level 1 pediatric trauma center as evidenced by improved teamwork scores and secondary survey completion on video review of live trauma activations.